FROM LAND REFORM TO POO PROTESTING: SOME THEOLOGICAL REFLECTIONS ON THE ECOLOGICAL REPERCUSSIONS OF ECONOMIC INEQUALITY - Conradie, Ernst M. (Scriptura, 2014)
This article consists of three distinct parts. The first part offers a number of observations on land as a lens to interpret economic inequalities in South Africa. The second part extrapolates such observations to explore the ecological dimensions of urban land reform with specific reference to the ongoing service delivery protests over sanitation (dubbed ‘poo protesting’) as reported in the media and more specifically in the Cape Times. The third part offers some theological and ethical reflections on the human need for sanitation as a form of internal critique of the engagement with such service delivery protests by the so-called ‘Concerned Citizens Group’ in which the author was involved.